Thermodynamic Properties and Crystallographic Characterization of Semiclathrate Hydrates Formed with Tetra-n-butylammonium Glycolate - Muromachi, Sanehiro (ACS Omega, 2019)
[Image: see text] Semiclathrate hydrates are a crystalline host–guest material, which forms with water and ionic substances such as tetra-n-butylammonium (TBA) salts. Various anions can be used as a counter anion to the TBA cation, and they can modify thermodynamic properties of the semiclathrate hydrates, which are critical for applications, for example, cold energy storage and gas separation. In this study, the semiclathrate hydrates of the TBA glycolate were newly synthesized. Measurements for melting temperatures and a heat of fusion and a crystal structure analysis were performed. In comparison with the other similar materials, such as acetates, propionates, lactates, and hydroxybutyrates, the glycolate greatly changed the melting temperature and the heat of fusion. The preliminarily determined crystal structure showed that the glycolate anion builds a relatively porous structure compared to the previously reported hydrates formed with hydroxycarboxylates. The present study showed that substitution of a hydrophobic group by a hydrophilic group is an effective method to control the thermodynamic properties as well as to improve environmental, biological, and chemical properties.